Differences in Perceptions Between Parents and Teachers on Online Learning During the COVID-19 Pandemic - Ade Ubaidah; Fatayah Fatayah; Yuni Susilowati; Ana Merdekawaty; Rima Rahmaniah; Syaharuddin Syaharuddin (Universitas Muhammadiyah Mataram, 2021)
Government policy to enforce online learning during the COVID-19 pandemic that is not supported by adequate facilities has become a significant obstacle for students and their parents. Each educational institution has different perspectives and perceptions. Therefore, this study aims to analyze the difference in perception between parents and teachers towards the implementation process and evaluation system of online learning. The data was collected using questionnaires of 17 indicators using the Unified Theory of Acceptance and Use of Technology (UTAUT) model criteria, then distributed online using random sampling techniques to parents and teachers throughout Indonesia at the elementary, junior high, and high school levels so that 118 data were obtained divided into 81 teachers and 37 parents. The results of the student test (t-test) obtained information that there is a difference in perception between parents and teachers, this can be seen from the t-test score of 1,919 with a sig score. 0.057. This is also evidenced by the average teacher response score of 66.19 which means positive, while the average response score of parents is 60.54 which means less positive to the application of online learning during COVID-19. The results of this study are expected to be used as an evaluation of online learning for the government in the future.